Overview of TB Patient Compliance for Control during the Covid-19 Pandemic at the UGM RSA TB Clinic - Avidati, Herfis; Harianto, Suci Wahyu; Ulfah, Undatun; Nurlaily, Arinda Nia; Tejaningrum, Krista Dyah (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
Tuberculosis (TB) is a public health problem that is a global challenge and is the third leading cause of death in Indonesia and the first leading cause of death due to infectious diseases. Based on data from the Ministry of Health of the Republic of Indonesia, there has been a decrease in the number of TB cases found and treated. As one of the strategies to control risk factors for TB disease transmission, RSA UGM provides a special clinic for TB patients whose rooms meet national standards. However, several times researchers found that there were still TB patients who controlled outside the TB clinic schedule so that they mingled with non-TB patients, which resulted in increasing the risk of TB disease transmission to patients visiting the UGM Hospital. The World Health Organization (WHO) declared Covid-19 a pandemic on 9 March 2020. This has caused public fear to visit health facilities. This study aims to determine the level of compliance of TB patient visits during the Covid-19 pandemic at the UGM RSA TB Clinic. This descriptive observational study used secondary data, with a total sampling technique and analyses using univariate analysis. Of the 40 samples that met the inclusion and exclusion criteria, 92.5% of patients were in the productive age range (18-65 years), mostly male (70%). The proportion of patients with pulmonary TB was 62.5% and the remaining 37.5% were extra- pulmonary TB patients. There was an increase in adherence of TB patients to control at the TB clinic and on schedule from month 1 to the following months.